Pengaruh Metode Mengajar Guru, Kebiasaan Belajar Siswa, Perhatian Orang Tua dan Orientasi Nilai Budaya terhadap Prestasi Belajar Akuntansi Dasar Siswa Kelas X AKL di SMK Negeri 2 Padang Tahun Ajaran 2020/2021 - Desi Ramadhani; Ansofino Ansofino; Yesmira Syamra (Horizon, 2021)
This study aims to analyze 1.) teacher teaching methods affect learning achievement 2.) student study habits affect learning achievement 3.) parental attention affects learning achievement 4.) cultural value orientation affects learning achievement 5.) teaching methods teachers, student study habits, parental attention and cultural value orientation have a simultaneous effect on the basic accounting learning achievement of class X AKL students iat SMK Negeri 2 Padang. This type of research is associative and descriptive. The population of this study was the students of class X AKL SMK Negeri 2 Padang totaling 180 people. The sampling technique used stratified random sampling with a total sample of 80 people. Data analysis using multiple linear regression analysis and hypothesis testing using f test and t test. Data analysis was assisted by SPSS version 16 and eviews version 8. The results of the study show that: 1.) Teacher's teaching methods greatly affect learning achievement, a greater influence is found in the sample group of workers 2.) Student learning habits greatly affect learning achievement, a greater influence is found in the sample group of workers, 3.) Parents' attention greatly affects learning achievement. The greater influence is found in the non-labor sample group. 4.) Cultural value orientation greatly affects learning achievement, the greater influence is found in the labor sample group.Kata Kunci : Prestasi , Metode, Kebiasaan, Perhatian, Orientasi